2022
DOI: 10.1002/hep4.2033
|View full text |Cite
|
Sign up to set email alerts
|

Up‐regulated LRRN2 expression as a marker for graft quality in living donor liver transplantation

Abstract: The quality and size of liver grafts are critical factors that influence livingdonor liver transplantation (LDLT) function and safety. However, the biomarkers used for predicting graft quality are lacking. In this study, we sought to identify unique graft quality markers, aside from donor age, by using the livers of non-human primates. Hepatic gene microarray expression data from young and elderly cynomolgus macaques revealed a total of 271 genes with significantly increased expression in the elderly. These ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Donor age has been used as a marker for graft quality in LDLT (18). However, liver graft quality does not uniformly decline with donor age, and it is important to assess individual changes in donor grafts because there are individual differences in aging (29). In addition, the several qualitative assessment methods previously reported require liver biopsy (30,31), while this IMAC examination is not invasive, and the IMAC can be measured with CT images obtained before surgery, with no additional burden on the donor.…”
Section: Discussionmentioning
confidence: 99%
“…Donor age has been used as a marker for graft quality in LDLT (18). However, liver graft quality does not uniformly decline with donor age, and it is important to assess individual changes in donor grafts because there are individual differences in aging (29). In addition, the several qualitative assessment methods previously reported require liver biopsy (30,31), while this IMAC examination is not invasive, and the IMAC can be measured with CT images obtained before surgery, with no additional burden on the donor.…”
Section: Discussionmentioning
confidence: 99%
“…Liver cirrhosis represents a major health burden worldwide, and the most common causes of cirrhosis are hepatitis C, alcohol-associated liver disease, and non-alcohol-associated liver disease. 1 Liver transplantation (LT) has been accepted as the most effective treatment for end-stage liver disease, 2,3 and various studies have shown improvement in the prognosis after LT. 4 The gut microbiota (GM) contributes to various physiological processes such as nutrient metabolism, maintenance of gut barrier integrity, immune modulation, and production of bioactive metabolites. 5 Recent advances in research have highlighted the intricate relationship between GM and liver function, emphasizing the importance of the gut-liver axis in the pathogenesis of liver cirrhosis.…”
Section: Introductionmentioning
confidence: 99%
“…Liver cirrhosis represents a major health burden worldwide, and the most common causes of cirrhosis are hepatitis C, alcohol‐associated liver disease, and non‐alcohol‐associated liver disease. 1 Liver transplantation (LT) has been accepted as the most effective treatment for end‐stage liver disease, 2 , 3 and various studies have shown improvement in the prognosis after LT. 4 …”
Section: Introductionmentioning
confidence: 99%